2020
DOI: 10.1038/s41598-020-59403-7
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of chemical to mechanical energy by the nucleotide binding domains of ABCB1

Abstract: P-glycoprotein (ABCB1) is an important component of barrier tissues that extrudes a wide range of chemically unrelated compounds. ABCB1 consists of two transmembrane domains forming the substrate binding and translocation domain, and of two cytoplasmic nucleotide binding domains (NBDs) that provide the energy by binding and hydrolyzing ATP. We analyzed the mechanistic and energetic properties of the NBD dimer via molecular dynamics simulations. We find that MgATP stabilizes the NBD dimer through strong attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…We used MD simulations to probe into the molecular origin of the restored transport function. We previously showed for wild-type ABCB1 that ATP binding stabilizes the NBD dimer by~42 kJ/mol and that the hydrolysis products ADP and inorganic phosphate create a high energy state that induces NBD separation [67,68]. Our simulations revealed that binding of ATP and its interactions with NBS1 are similar for wild-type ABCB1 and the catalytic glutamate mutant, but showed more restricted dynamics in the E556M mutant, indicating stronger interactions that are consistent with a locked state.…”
Section: Plos Geneticsmentioning
confidence: 50%
See 3 more Smart Citations
“…We used MD simulations to probe into the molecular origin of the restored transport function. We previously showed for wild-type ABCB1 that ATP binding stabilizes the NBD dimer by~42 kJ/mol and that the hydrolysis products ADP and inorganic phosphate create a high energy state that induces NBD separation [67,68]. Our simulations revealed that binding of ATP and its interactions with NBS1 are similar for wild-type ABCB1 and the catalytic glutamate mutant, but showed more restricted dynamics in the E556M mutant, indicating stronger interactions that are consistent with a locked state.…”
Section: Plos Geneticsmentioning
confidence: 50%
“…Transporters were stable in all simulations, maintaining their secondary and tertiary structures and showing similar deviations from their respective starting conformations. Detailed analysis showed that the Pγ of ATP interacts with the Mg 2+ ion, the Walker A motif and the signature sequence, while the Pα and Pβ almost exclusively interact with the Walker A motif (Fig 6) [67,68]. Histograms of distances measured between the Cα atom of S434 (first turn of the Walker A helix) and the Pα of ATP showed equally stable interactions in the three variants, with a similar degree of fluctuations ( Fig 6A).…”
Section: The Nbs1 Mutations Change the Molecular Mechanism Of Atp Binmentioning
confidence: 86%
See 2 more Smart Citations
“…ATP hydrolysis is asymmetric in ABC transporters with a degenerate site, leading to a high energy state [44,45] in the canonical NBS2 (MgADP + Pi) after hydrolysis of ATP, while degenerate NBS1 contains the nonhydrolyzed ATP. Accordingly, NBD separation will most likely be asymmetric, as MgATP bound to NBS1 represents a low energy state [44,45] that stabilizes the closed NBS1 and thus glues the NBDs together. The motions of NBD separation could in theory still be coordinated and symmetric, if other parts of the transporter would enforce such symmetric motion, similar to hemoglobin, which seems to operate using concerted motion of all four hemoglobin subunits in response to oxygen binding [46].…”
Section: Conformational (A)symmetry In Crystal and Cryo‐em Structuresmentioning
confidence: 99%